Kategoria praw dziecka w refleksji dydaktyki akademickiej - Turczyk, Małgorzata (Kultura-Społeczeństwo-Edukacja, 2018)
Turczyk Małgorzata, Kategoria praw dziecka w refleksji dydaktyki akademickiej [The category of children’s rights in the reflection of academic didactics]. Kultura – Społeczeństwo – Edukacja nr 2(14) 2018, Poznań 2018, pp. 119–126, Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2018.14.10. This paper concerns the place and meaning of a new category of children’s rights, which also finds its place in the area of interest of academic didactics. The current approach to human rights in schooling is basically normative, thus, the present academic didactics is challenged to prepare students of education – and teaching – related faculties to confront the issues in the field of children’s rights at work in a professional manner. The paper illustrates an author’s concept of didactics in terms of education to children’s rights at higher schools which was elaborated based of the research on the didactic aspects of children’s rights education for teachers and educationists on the academic level. The following issues were put in question and served as a basis for specific approaches to academic didactics in terms of education on children’s rights: an essence and need for inclusion of content related to children’s rights in academic learning practice, didactic tools at teacher’s disposal and their role in education for children’s rights. On the one hand, the paper presents a discussion on theprofessional preparation of teachers and educationists to face challenges related to protection and promotion of children’s rights within educational environments. On the other hand, it includes an attempt to merge the discrepancy between theory and practice in this field.